2nd International Symposium : Frontiers in Anatomy and Physiology Research and Education - Angela, Siner; Marina, Kapitonova; Sergey, Dydykin; Igor, Zadnipryany; Vladimir, Nikolenko; Larisa, Udochkina; Siti Nurma Hanim, Hadie; Rhun Yian, Koh; Wan Zuhainis, Saad; Muhammad Hamdi, Mahmood; Alexey, Smirnov; Olga, Fedorova; et al. (2025)
The aim of the special issue is to expand knowledge on the recent achievements in Anatomy, Physiology and related basic, preclinical, and clinical sciences of the participants of the 2nd International Symposium: Frontiers in Anatomy and Physiology Research and Education, conducted by the Faculty of Medicine and Heath Sciences, Universiti Malaysia Sarawak, in collaboration with the international partners on December 13-14, 2023, to strengthen international collaboration between Malaysian and overseas universities and to help all the readers of the journal to identify their own niche in research and international partnership. It is also aimed at motivation of young researchers to participate in the research competitions and win, to upgrade their own research and participate in the scientific networking. The scope of the publications in the Special Issue covers but is not limited to the scientific data obtained from research in clinical anatomy, histology, embryology, systemic physiology and pathophysiology, molecular medicine, physiology of cell membrane and single cells, histophysiology, animal studies, drug discovery, immunology and infectious diseases, inflammation and cancer, neurosciences and medical education. The keynote and the invited speakers are world-renowned scientists and physicians known for cutting-edge research and clinical practice. The papers and abstracts were peer-reviewed and selected for publication by the scientific committee of the Symposium formed by Malaysian and international researchers.